FOOD SECURITY CHALLENGES AND POLICY RESPONSES IN SOUTH SULAWESI : TOWARD SUSTAINABLE SELF-SUFFICIENCY - Zulkifli, Zulkifli; Dahliana, Besse; Suhartina, Suhartina (PT. Jurnal Center Indonesia Publisher, 2025)
This study analyzes the challenges of food security and the policy responses of the government in achieving food self-sufficiency in South Sulawesi in 2025. The research aims to identify production-consumption gaps, distribution bottlenecks, and the impacts of climate variability and agricultural policies on food availability, accessibility, and affordability. A mixed-methods approach was employed, combining qualitative and quantitative techniques through household surveys, in-depth interviews with farmers and policymakers, field observations, and secondary data from the Central Statistics Agency and the South Sulawesi Agricultural Department. The results reveal persistent production deficits for rice and soybeans, while corn has reached a surplus, illustrating structural imbalances among staple commodities. Approximately 62% of respondents reported difficulties in transportation and storage due to inadequate infrastructure, contributing to post-harvest losses and unstable food prices. Government programs such as irrigation development, input subsidies, and farmer training have provided partial benefits, yet 57% of farmers indicated irregular access to such support. Moreover, climate shocks such as El Niño continue to depress yields and increase vulnerability among smallholder farmers. Conversely, social capital, manifested in farmer groups and cooperative networks, has played a significant role in sustaining household food availability and resilience. The findings suggest that food security in South Sulawesi cannot be addressed solely through production increases. A multifaceted strategy is required, emphasizing rural infrastructure development, climate-smart agricultural innovation, institutional and irrigation reform, and community-based mechanisms that strengthen social capital. This integrative approach provides empirical evidence for policy design and contributes to the broader discourse on sustainable food self-sufficiency in Indonesia.